What Is New in the 2023 European Society of Cardiology Guidelines for the Management of Acute Coronary Syndromes - Marco Roffi (Cardiology Discovery)
For the first time, European Society of Cardiology (ESC) guidelines have aggregated in 1 single document recommendations for the management of patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS) and ST-elevation myocardial infarction (STEMI). From a clinical perspective, this is coherent, as the spectrum of clinical presentations in acute coronary syndromes (ACS) may range from new onset or progressive troponin-negative angina to STEMI, cardiogenic shock, or cardiac arrest. In addition, the management pathways of NSTE-ACS and STEMI patients are widely similar. Compared with previous editions of the guidelines, the extensive document is improved also from a graphic perspective, containing several appealing and easy-to-understand figures. New or modified recommendations include, among others, the topics of diagnostic work-up, timing of invasive strategy, revascularization in multi-vessel disease, intravascular imaging, cardiac arrest, cardiogenic shock, and antithrombotic treatment. For the first time in the field of ACS, ESC guidelines have incorporated a section on patient perspectives with dedicated recommendations. Some of the most relevant changes in recommendations impacting clinical practice are discussed in this article.